Enhanced Non-Invasive Diagnosis of Female Urinary Incontinence Using Static and Functional Transperineal Ultrasonography - Milosz Pietrus; Kazimierz Pityński; Maciej W. Socha; Iwona Gawron; Robert Biskupski-Brawura-Samaha; Marcin Waligóra (Diagnostics, 2024)
Background/Objectives: To investigate the utility of transperineal ultrasound in detecting stress urinary incontinence (SUI) and identify optimal anatomical and functional parameters. Methods: Thirty-four women presenting with SUI with or without pelvic organ prolapse between 2012 and 2016 were studied. The control group included patients without SUI who underwent surgery for mild gynecologic disorders or pelvic organ prolapse. The relationship between selected ultrasound parameters and SUI was determined. Results: Among the 20 variables measured in ultrasonography using 4 angles and the bladder–symphysis distance (BSD) values, we found that the difference in the BSD obtained at rest and during the Valsalva maneuver (odds ratio [OR]: 1.15, 95% confidence interval [CI]: 1.05–1.27, p = 0.004), the mean urethral diameter (UD; OR: 4.29, 95% CI: 2.07–8.83, p = 0.0001), and the occurrence of the funneling sign during the Valsalva maneuver (OR: 21; 95% CI: 6.1–71.9, p < 0.0001) were associated with urinary incontinence in the logistic regression analysis. The optimal cut-off point for BSD was >8 mm (area under the curve (AUC), 0.71; sensitivity, 91.2%; specificity, 56.8%; p = 0.001) and that for UD was >6 mm (AUC, 0.84; sensitivity, 82.1%; specificity, 73%; p < 0.001). Conclusions: Transperineal ultrasonography is a useful tool for detecting SUI. Our findings highlighted the utility of several sonographic parameters, mainly the urethral diameter, in the diagnosis of urinary incontinence.